Experimental Study on Phase Change Thermal Storage of Crystalline Hydrated Salt Applied in Solar Thermal Utilization. (2017) - Wang, Zanshe; Yang, Lisheng; Hu, Juntao; Hu, Xianwei; Gu, Zhaolin
Abstract: The building energy consumption is 28 percent of the total energy consumption in China, especially in winter building heating. The solar energy is a high quality clean and renewable energy for building energy conservation, however, the solar energy is easily affected by the weather and the demands of heating is often in the light. Therefore, the thermal storage technology can solve these two contradictions and can be used as energy storage pool in order that it can storage solar energy in day and release heat in night. In this study, the phase change thermal storage material of crystalline hydrated salt Na2 HPO4 12H2 O is adopted as the basic thermal storage material, additionally, different content of alumina powder and sodium carboxymethyl cellulose are added in the basic thermal storage material as nucleating agent and thickening agent, according to the tests, the step curve, the subcooling curve and the latent heat curve are obtained. The results show that the phase change thermal storage material is better in stability when the ratio is that the water 30%, the alumina powder 2%, the sodium carboxymethyl cellulose 5% and the Na2 HPO4 12H2 O 63%, the phase change temperature is around 36.0℃, the subcooling temperature is 4.6℃, and the phase change latent heat is 182.4kJ/kg.